Application of theory of planned behavior to predict recreational sports activities participation of students in Malaysia - Chun, Cheng Chuan; Yusof, Aminuddin; Chee, Chen Soon; Abdullah, Maria Chong (University of Pitesti, 2014)
This study aims to understand the factors that influence the participation of high school students in recreational sports activities using the “Theory of Planned Behavior” (TPB) (Ajzen, 1991). Questionnaires that were adapted from Cunningham and Kwon (2003) were used to measure the reasons for participation of recreational sports among high school students in Malaysia. The respondents consisted of 101 high school students from the age of 13 to16. Analyses of data include descriptive statistics, Pearson Product-Moment‘s correlation and standard multiple regression. The findings showed that there is a significant relationship between attitude factor and subjective norms with behavioral intention to participate in recreational sports activities. This study proposed intervention measures to increase the participation of high school students in recreational sports in Malaysia.